Evaluation of the Families SHARE workbook: an educational tool outlining disease risk and healthy guidelines to reduce risk of heart disease, diabetes, breast cancer and colorectal cancer. (December 2015) - Koehly, Laura; Morris, Bronwyn; Skapinsky, Kaley; Goergen, Andrea; Ludden, Amanda
Abstract Background Common diseases such as heart disease, diabetes, and cancer are etiologically complex with multiple risk factors (e.g., environment, genetic, lifestyle). These risk factors tend to cluster in families, making families an important social context for intervention and lifestyle-focused disease prevention. The Families Sharing Health Assessment and Risk Evaluation (SHARE) workbook was designed as an educational tool outlining family health history based risk of heart disease, type 2 diabetes, breast cancer, and colorectal cancer. The current paper describes the steps taken to develop and evaluate the workbook employing a user-centered design approach. Methods The workbook was developed in four steps, culminating in an evaluation focusing on understanding and usability of the tool. The evaluation was based on two Phases of data collected from a sample of mothers of young children in the Washington, D.C., area. A baseline assessment and follow-up approximately two weeks after receipt of the workbook were conducted, as well as focus groups with participants. The design of the workbook was refined in response to participant feedback from the first evaluation Phase and subsequently re-evaluated with a new sample. Results After incorporating user-based feedback and revising the workbook, Phase 2 evaluation results indicated that understanding of the workbook components improved for all sections (from 6.26 to 6.81 on a 7-point scale). In addition, 100 % of users were able to use the algorithm to assess their disease risk and over 60 % used the algorithm to assess family members' disease risk. At follow-up, confidence to increase fruit, vegetable and fiber intake improved significantly, as well. Conclusions The Families SHARE workbook was developed and evaluated resulting in a family health history tool that is both understandable and usable by key stakeholders. This educational tool will be used in intervention studies assessing the effectiveness of family genomics health educators who use the Families SHARE workbook to disseminate family risk information and encourage risk reducing behaviors. Trial registration ClinicalTrials.gov, NCT01498276 . Registered 21 December 2011